Qualitative Research on Expanded Prenatal and Newborn Screening: Robust but Marginalized - Grob, Rachel (The Hastings Center report, 2019)
If I told you that screening technologies are iteratively transforming how people experience pregnancy and early parenting, you might take notice. If I mentioned that a new class of newborn patients was being created and that particular forms of parental vigilance were emerging, you might want to know more. If I described how the particular stories told about screening in public, combined with parents’ fierce commitment to safeguarding their children’s health, make it difficult for problematic experiences with screening to translate into negative opinions about it, you would most likely be intrigued. An extensive qualitative literature documents all these social phenomena, and more, in connection with the spread of prenatal and newborn screening. So why is it, then, that commentators frequently assert that the predicted psychosocial impact of increased screening and testing associated with “the genomic revolution” has been far less severe and worthy of attention than predicted? How can or should social science “evidence” that sits outside adopted measurement conventions be considered? Why is it that summary statements about the psychosocial impact of genomic information often ignore qualitative evidence, or sideline it as relevant only for improving communication among patients, clinicians, and public health systems? This essay addresses such questions, using qualitative research on prenatal and newborn screening as a case study for illustrating the broad methodological, ideological, and dialogical issues at stake.